The concept of Wasatiyyah and the challenge of Islam liberal in Indonesia - Hassan, Mohd. Kamal (2010)
My research shows that the justly balanced worldview of Islam has wide implications for contemporary Muslim society encompassing the Muslims’ religiosity, spirituality, intellectuality, outlook, attitudes, behaviour, relationships and activism. Each one of the twenty positions spelled out by al- Qaradhawi also serves as general principles and guidelines towards achieving the goals of Islamic moderation, and avoid the tendency of Muslim societies to be caught between the two poles of immoderation (ifreet) and negligence (tafreet). In addition to the above twenty “middle path” positions that Muslims have to adopt, al-Qaradhawi mentions eight basic religious implications which Muslims need to take note of in pursuing the path of al-Wasatiyyah. The rise of “Islam Liberal” movement in Indonesia is a serious internal challenge to the true meaning of Wasatiyyah. A comparison with a Singaporean Muslim stand will show the deviationist tendency of the “Islam Liberal Network”.